Analisis Deiksis pada Antologi Cerpen Dompet Bolu Kukus sebagai Bahan Ajar Sekolah Dasar - Nada, Amallia; Widjojoko, Widjojoko; Wardana, Deni (Didaktika, 2021)
Language is a connecting tool that is needed as a means of communication. Therefore, it’s use in daily activities facilitates interaction, either directly or indirectly, written or unwritten. Language skills in Indonesian language learning have four forms, namely speaking, writing, listening and reading skills. writing and speaking skills can be called to productive competence, while listening and reading skills appertain receptive competence. The use of language in communication provides convenience, one of which is the reference and referential system. Behind this convenience, the referral system can also cause ambiguity, confusion and misunderstanding. This diexist analysis study aims to examine the contents of the short story anthology Dompet Bolu Kukus that can be used in the Indonesian language learning process. Deixis has a function to explain the meaning of speech so that the meaning contained in the speech can be clearly understood by the reader, a review related to this deixis is a way to discover connection between language and context from the language structure it self, so it is necessary to look at who, when and where the word was pronounced to find the meaning of a word. The results of this diexist study can be used as teaching materials for elementary school students because it has the potential to be a reference material in understanding the structure of Indonesian